Microplastics on plankton samples: Multiple digestion techniques assessment based on weight, size, and FTIR spectroscopy analyses - Alfonso, María Belén (2021)
Digestion protocols are needed to determine microplastics abundance and features. This study assessed the organic matter (OM) digestion efficiency on plankton samples and the MPs´ weight, size, and polymer changes under different digestion techniques. For this, 2-step (KOH and H2O2 + Fe2+) and 3-step (2-step and enzymes) digestion techniques were assessed under different duration and temperature conditions. The results obtained for OM digestion with 2-step and 3-step techniques were satisfactory. Weight changes were registered for polyethylene terephthalate (PET), polystyrene foam, polyvinyl chloride, and polycarbonate with 2-step digestion, but with inconsistent values. Significant size changes were registered only for PET applying 2-step digestion techniques at 60 °C. Using 40 °C for 72 h prevailed all polymers from size changes. Polyethylene weathered MPs were also preserved, including an enzymatic step. Polymer fingerprints were not affected by any digestion technique. Based on these results, any method applying high temperatures will damage MPs.